Battering in neurological patients - Paz Rodríguez, Francisco; Sánchez Guzmán, María Alejandra (Anales de Psicología / Annals of Psychology, 2010)
The purpose of this article is to describe the relationship be- tween demographic and emotional variables of caregivers and mistreat- ment towards patients with neurological diseases. The study is a cross sectional survey that used sample of 110 caregivers of patients attended at Institute National of Neurology and Neurosurgery. Sociodemographic variables, perception of stress, coping strategies; anxiety and depression, overwork, activities of the daily life and mistreatment towards patients were assessed. We used various statistical tests to determine significant relationships between variables against abuse and perceived stress. 39 % of caregivers reported mistreatment. 70% of the patients had a primary care- giver and 77% of patients did not have financial support. Mistreatment was perpetrated by spouse in 42% of the cases. The structural and subjec- tive context in which the patients develop is favorable violence in the relation patient caregiver and is not recognized as a problem of public health.